2020
DOI: 10.1016/j.ijid.2020.06.045
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human thrombopoietin in critically ill patients with sepsis-associated thrombocytopenia: A clinical study

Abstract: Background: Sepsis causes varying degrees of thrombocytopenia that are closely related to the likelihood of patient mortality. This study analysed the effect of recombinant human thrombopoietin (rhTPO) on the platelet count in critically ill patients with sepsis-associated thrombocytopenia and provided a reference for its treatment. Material/methods: The study was a retrospective analysis of the clinical data of patients. Patients were divided into an rhTPO group and control group according to rhTPO use during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…In recent years, several studies have suggested that rhTPO could rapidly lead to a recovery of the platelet count, increase the number of survival days and reduce the 28‐day mortality rate in sepsis patients with severe thrombocytopenia [10, 12]. Nevertheless, another study found that rhTPO was efficacious in increasing the patients' platelet counts, resulting in a shorter ICU stay (9.20 ± 5.38 vs. 10.88 ± 6.82 days, p = 0.047) for patients with severe thrombocytopenia and patients with severe sepsis, while there was no significant difference in 28‐day mortality (rhTPO group: 25.0% vs. control group: 34.1%, p = 0.158) [25]. Therefore, the question of whether patients with sepsis‐induced thrombocytopenia can benefit from rhTPO therapy still remains according to the controversial results.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several studies have suggested that rhTPO could rapidly lead to a recovery of the platelet count, increase the number of survival days and reduce the 28‐day mortality rate in sepsis patients with severe thrombocytopenia [10, 12]. Nevertheless, another study found that rhTPO was efficacious in increasing the patients' platelet counts, resulting in a shorter ICU stay (9.20 ± 5.38 vs. 10.88 ± 6.82 days, p = 0.047) for patients with severe thrombocytopenia and patients with severe sepsis, while there was no significant difference in 28‐day mortality (rhTPO group: 25.0% vs. control group: 34.1%, p = 0.158) [25]. Therefore, the question of whether patients with sepsis‐induced thrombocytopenia can benefit from rhTPO therapy still remains according to the controversial results.…”
Section: Discussionmentioning
confidence: 99%
“…In another research, it suggested that rescue therapy with rhTPO could rapidly lead to a recovery of the platelet count, increase survival days and reduce the 28-day mortality in sepsis patients with severe thrombocytopenia (25). Nevertheless, Yu Liu et al found that rhTPO is e cacious in increasing the patients' platelet counts, resulting in a shorter ICU stay time (9.20 ± 5.38 vs 10.88 ± 6.82, p = 0.047) for patients with severe thrombocytopenia or patients with severe sepsis, while there was no signi cant difference in 28-days mortality ( rhTPO group: 25.0% vs. control group: 34.1%, p = 0.158) between the two groups (26). Therefore, whether patients with sepsis-induced thrombocytopenia can bene t from rhTPO therapy still remains a question according to the controversial results.…”
Section: Discussionmentioning
confidence: 97%
“…TPO is a thrombopoietic growth factor produced by the liver that expressly regulates the release of platelets. Studies have found that recombinant human thrombopoietin (rhTPO) can reduce platelet and red blood cell transfusions in IRH patients (12,22).…”
Section: Discussionmentioning
confidence: 99%